Degradation of the northern paraná landscape: a study on forest fragments/ Degradação da paisagem norte-paranaense: um estudo de fragmentos florestais - Efraim Rodrigues; Amarildo Souza de Paula (Semina: Ciências Agrárias, 2002)
Due to a fast occupation process, nearly all of the native vegetal covering of northern Paraná was devastated. Considering the lack of basic studies that support the management of forest remainders, this dissertation studies the forest fragmentation of the landscape in a transect of 180 km (between Maringá and Jacarezinho), considering a time and/or age of occupation gradient. One has adopted the hypothesis that the landscape to west, colonized from 1930 (Londrina) and 1947 (Maringá), suffered smaller degradation in a comparison with what happened in the landscape situated further to east (and colonized in the mid 19th century and early 20th century). Results demonstrated that the initial hypothesis should be refute. Historical and factors socioeconomic influenced the occupation way and, consequently, the distribution of the forest fragments in the landscape. Devido ao rápido processo de ocupação, quase toda cobertura vegetal nativa do Norte do Paraná foi devastada. Considerando a necessidade de estudos básicos que dêem suporte ao manejo de remanescentes florestais, este trabalho estuda a fragmentação florestal da paisagem num transecto de 180 km (entre Jacarezinho e Maringá). Adotou-se a hipótese de que a paisagem mais a oeste – colonizada a partir de 1930 (Londrina) e 1947 (Maringá) – sofreu menor degradação antrópica, em comparação a paisagem, situada mais à leste (colonizada em meados do século XIX e início do século XX). Os resultados demonstraram que a hipótese inicial deve ser refutada. Fatores históricos e socioeconômicos influenciaram o modo de ocupação e conseqüentemente, a distribuição dos fragmentos florestais na paisagem.